Clima organizacional y el desempeño laboral en colaboradores de Compartamos Financiera S.A de Loreto marzo 2021 - Hidalgo Peña, Karen Melisa (2021)
The research is titled Organizational Climate and Labor Performance in the Employees of we behave Financial S.A. of Loreto, March 2021 and, its main purpose is to Establish the Relationship between Organizational Climate and Work Performance in Collaborators of we behave Financial SA of Loreto March 2021 and as specific objectives to determine which of the elements of the quality of the service has greater perception by the client the level of Organizational Climate in Collaborators of we behave Financial SA of Loreto March 2021 and determine the level of Labor Performance in Collaborators of we behave Financial S. A. of Loreto march 2021. The research concludes that the relationship between Organizational Climate and Work Performance in employees of we behave Financial S.A. of Loreto, March 2021 is direct moderate and significant, with a Spearman Rho correlation coefficient of 0.483, a p valius of 0.007 and a chi-square value of 18.24, p = 0.000 Kendall's Tau-b = 0,440